An overview of antifungal peptides derived from insects - Faruck, Mohammad Omer; Yusof, Faridah; Chowdhury, Silvia (Elsevier Inc., 2016)
Fungi are not classified as plants or animals. They resemble plants in many ways but do not produce chlorophyll or make their own food photosynthetically like plants. Fungi are useful for the production of beer, bread, medicine, etc. More complex than viruses or bacteria; fungi can be destructive human pathogens responsible for various diseases in humans. Most people have a strong natural immunity against fungal infection. However, fungi can cause diseases when this immunity breaks down. In the last few years, fungal infection has increased strikingly and has been accompanied by a rise in the number of deaths of cancer patients, transplant recipients, and acquired immunodeficiency syndrome (AIDS) patients owing to fungal infections. The growth rate of fungi is very slow and quite difficult to identify. A series of molecules with antifungal activity against different strains of fungi have been found in insects, which can be of great importance to tackle human diseases. Insects secrete such compounds, which can be peptides, as a part of their immune defense reactions. Active antifungal peptides developed by insects to rapidly eliminate infectious pathogens are considered a component of the defense munitions. This review focuses on naturally occurring antifungal peptides from insects and their challenges to be used as armaments against human diseases.